The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1088/1757-899x/890/1/012187
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Development of Civil and Residential Real Estate Based on the Construction Waste Recycling

Abstract: The work is devoted to assessing the environmental and economic efficiency of construction waste recycling concerning the sustainable development of civil real estate. The crisis processes in the micro-and macro-level economy has a negative impact on the Russian investment and construction complex, which threatens the national task performance to provide affordable housing within implementation of the investment programs financed by municipal and federal budgets. It is shown that one of the directions of susta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…H avard et al (2007) predicted future waste management by estimating the level of activity in the construction waste industry to determine the relevant specific waste generation factors and by calculating the flow of waste into use and transferred to waste. Avilova et al (2020) evaluated the sustainable development of environmental and economic efficiency of construction waste recycling in civil real estate, and it found that the use of innovative recycling technology and the optimal design and selection of materials were conducive to the construction of real estate recycling resources. Cheng and Ma (2013) believed that the quantitative prediction of waste in developed cities such as Hong Kong was crucial for waste management.…”
Section: Literature Review 21 Recycling Of Construction Wastementioning
confidence: 99%
“…H avard et al (2007) predicted future waste management by estimating the level of activity in the construction waste industry to determine the relevant specific waste generation factors and by calculating the flow of waste into use and transferred to waste. Avilova et al (2020) evaluated the sustainable development of environmental and economic efficiency of construction waste recycling in civil real estate, and it found that the use of innovative recycling technology and the optimal design and selection of materials were conducive to the construction of real estate recycling resources. Cheng and Ma (2013) believed that the quantitative prediction of waste in developed cities such as Hong Kong was crucial for waste management.…”
Section: Literature Review 21 Recycling Of Construction Wastementioning
confidence: 99%